Development of a regional urogenital pain network: Sharing good practice. (April 2017) - Ogbonmwan, Daisy; Graham, Yitka; Hotonu, Oluseyi; Hussey, Jane
Abstract: Within the North East of England, there are an increasing number of complex patients presenting with urogenital pain; many of whom are under the care of multiple specialities. To understand and plan a cohesive strategy for this cohort, we have established a multi-disciplinary regional urogenital pain network meeting. The quarterly meetings allow us to share expertise, best practice and identify areas for improvement with the aim of therefore streamlining the patient journey and enhancing the quality of care patients with urogenital pain receive.